Analysis of investment environment and their role in attracting foreign investment period 2017-2021 - Fathel, Hiba (The Gulf Economist, 2023)
The importance of the investment environment has become one of the important strategic economic issues for investment and overall economic development and development. Therefore, developing countries pay special attention to improving their investment environment through a variety of means, including changes in investment laws, incentives, facilities and guarantees they provide, as well as facilitating procedures for obtaining licenses and providing appropriate infrastructure for the business sector. From this standpoint, competition intensified between countries to obtain the best ranking in global indicators that highlight the role of the investment climate. As for Iraq, it occupies a low rank in international indicators because it is located in countries that do not enjoy economic freedom, and a low degree in the Corruption Perceptions Index, medium in human development, and lagging in globalization, in addition to the confusion of the Iraqi government and the National Investment Council in creating an appropriate investment environment that bears the elements of a successful environment. The aim of the research is to know the impact of the investment environment indicators on attracting and encouraging investment, the research used the questionnaire method because it was not possible to obtain all the data related to the research, and the most important conclusions reached by the research is that foreign investment has a major role in developing the competitiveness of the country, whether between internal sectors or With other countries, the research also found that the Iraqi investment environment is an attractive environment for foreign investment, but it lacks many of the ingredients that attract investment.